Comparison of Dexmedetomidine and Dexamethasone as an Adjuvant to Bupivacaine in Onset and Interval of Supraclavicular Nerve Block - Neeta Devi, Vijai Kumar, Arsalan Jamil, Shumaila Ali, Zahid Aziz Soomro, Aimen Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare duration and onset of motor and sensory block by using dexmedetomidine and dexamethasone as adjuvant to bupivicaine in supraclavicular brachial plexusblock. Place and duration of study: Department of Anaesthesiology, Surgical Intensive Care & Pain Management, Civil Hospital, Dow University of Health Sciences Karachi from 29th June 2022 to 29th December 2022. Design: Randomized controlled trial study Methodology: Sixty patientswere enrolled in the study that had an elective upper-limb surgery performed under supraclavicular anesthesia of hand, wrist, forearmand elbow were allocated through randomization into two groups. Thirty patients in group A treated with bupivacaine 25 ml of 0.5% with dexamethasone 8mg (2 ML) and 30 in group B treated with bupivicaine 25 ml of 0.5% with dexmedetomidine 1µg/kg (2ml). Patients were observed in post-anesthesiacareunitpost-surgery. Duration of onset of pain was noted by patient’s first request for analgesia. Results:Themean age of patients was 34.88±9.39 years. Mean onset time of sensory and motor block was significantly low in group A than group B. Mean duration of sensory block and motor block was significantly high in group B than group A [813.87±113.72 vs. 752.63±27.96; p=0.006] and [734.13± 84.44 vs533.07±88.38;p=0.0005]. The time to request for 1st rescue analgesic was significantly increased in group B as compare to group A(p=0.0005). Practical Implication: Regional anesthesia in orthopedic procedures is superior to general anesthesia in terms of better postoperative pain relief, less central nervous system depressant effect of drugs and early discharge from hospital. Conclusion:The duration of block prolonged in cases where dexmedetomidine was added to the bupivacaine was longer but onset was reduced in comparison to the dexamethasone cases. Keywords: Brachial plexus block, Supraclavicular block, Dexmedetomidine, Dexamethasone